Caffeine suppresses high-fat diet-induced body weight gain in mice depending on feeding timing. (December 2022) - Haraguchi, Atsushi; Yamazaki, Tomohiro; Ryan, Conn; Ito, Kaede; Sato, Shuhei; Tamura, Konomi; Sekiguchi, Masataka; Cao, Siyuan; Shibata, Shigenobu
Graphical abstract: Highlights: Effects of caffeine would vary depending on timing of intake. Caffeine at the begging of active period would inhibit weight by high-fat diet. Caffeine at the begging of active period would enhance clock gene expression rhythms. Caffeine at the begging of active period would suppress lipogenesis genes expression. Abstract: The time-dependent effects of caffeine intake on physiological functions remain to be investigated, although various effects of caffeine on physiological functions have been document. Therefore, the present study investigated the optimal timing of caffeine intake to produce an efficient anti-obesity effect. We prepared a high-fat diet (HFD) or HFD supplemented with 0.03% caffeine (HFD-caf) and regulated twice-daily 8-hour time-restricted feeding. Male Institute of Cancer Research mice were divided into three groups: group fed HFD alone (control), group fed HFD-caf at the beginning of the active period (BF-caf), and group fed HFD-caf at the end of the active period (DN-caf). The BF-caf group (42.8 ± 1.5 g) showed lower body weight than the other groups (control, 49.7 ± 2.1 g; DN-caf, 47.1 ± 1.3 g), although the three groups showed similar HFD intake levels. Therefore, caffeine intake at the beginning of the active period suppressed HFD-induced body weight gain.